SOCIAL AWARENESS (Discourse Analysis of Novel Dalang Galau by Sujiwo Tejo) - Hamzah, Adi Ari (UIN Kiai Ageng Muhammad Besari Ponorogo, 2020)
Abstract: Sujiwo Tejo is an Indonesian novel writer who is considered a writer as well as a contemporary humanist. The themes in his novels always raise social, political or religious issues. The novel